The Eschatological Rest of the Benjaminian Eingedenken: (Messianism and Secularization) - Alías, Antonio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This essay addresses the conceptualization process of Benjamin’s remembrance [Eingedenken], understood by the German thinker as a critical exercise on an idea of history that, since Hegel, has been assimilated to progress as the guiding principle of modern societies. Thus, by taking different epistemological assumptions, Walter Benjamin seeks in memory a new historical time to come, activated dialectically by certain messianism as an eschatological remainder in the field of a modern secularization.